2018
DOI: 10.15835/nbha46211110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial-algal Biostimulant on the Yield and Internal Quality of Lettuce (Lactuca sativa L.) Produced for Spring and Summer Crop

Abstract: Plant biostimulants can enhance crop nutrition status, stress tolerance, yield and quality in environment-friendly manner. The aim of this study was to determine the effect of an algae and bacteria preparations on the yield and nutritional parameters of leaf and romaine lettuce cultivated for spring and summer crop. The application of a combined biostimulant consisting of plant growth-promoting bacteria (Bacillus licheniformis, Bacillus megatherium, Azotobacter sp., Azospirillum sp., and Herbaspirillum sp.) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
4
26
0
1
Order By: Relevance
“…Therefore, the PBS30U5C system is the best choice among treatments because it presented the best result in the two plant growth evaluations performed. For comparison, the literature shows that the use of biostimulation fertilizing systems based on bacterial–algal preparation led to a significantly higher lettuce weight compared to the control, equal to 22.7% . In turn, the treatments with organic fertilizers increased the lettuce weight by 18% .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the PBS30U5C system is the best choice among treatments because it presented the best result in the two plant growth evaluations performed. For comparison, the literature shows that the use of biostimulation fertilizing systems based on bacterial–algal preparation led to a significantly higher lettuce weight compared to the control, equal to 22.7% . In turn, the treatments with organic fertilizers increased the lettuce weight by 18% .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a formulation composed of C. vulgaris and plant growth-promoting bacteria (Bacillus licheniformis, Bacillus megatherium, Azotobacter sp., Azospirillum sp., and Herbaspirillum sp.) showed to positively affect the fresh weight, total antioxidant capacity, and total carotenoids content in lettuce cultivated for spring and summer crop [16]. More recently, an extract from Scenedesmus quadricauda showed a biostimulant effect on lettuce seedlings, increasing their growth at shoot level, and by influencing the activities of several enzymes involved in the primary and secondary plant metabolisms [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lettuce (L. sativa L.) is one of the most important vegetable crops grown in the Mediterranean area; however, it is a moderately sensitive crop to salt, therefore the use of biostimulant is required as a very useful practice to enhance yield [23]. Kopta et al [24] found that a preparation based on microalgae (C. vulgaris) and plant growth-promoting bacteria (Bacillus licheniformis, Bacillus megatherium, Azotobacter sp., Azospirillum sp., and Herbaspirillum sp.) positively affected the yield and nutritional parameters of lettuce cultivated as a spring and summer crop by increasing the fresh weight, the total antioxidant capacity, and total carotenoid content.…”
Section: Introductionmentioning
confidence: 99%